2021
DOI: 10.3390/ijerph18020490
|View full text |Cite
|
Sign up to set email alerts
|

Secular Trends in Height, Body Mass and Mean Menarche Age in Romanian Children and Adolescents, 1936–2016

Abstract: Secular trends in anthropometric parameters have been documented in most European countries, but no data is available regarding Romanian. The aim of the study was to calculate secular trend in height, body mass and mean menarche age for Romanian children and adolescents. Methods: A secondary data analysis was performed using ten data sets for urban and eight data sets for rural boys and girls, age 5–15 years, covering 80 years (1936 to 2016). Secular trend in height (cm/decade), body mass(kg/decade) and mean m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Data from a Danish cohort of girls born between 2000 and 2003 estimated a menarche age of 13.0 years, occurring 3.6 months before the mothers’ menarche age (Brix et al, 2019). The data from five studies carried out between 1971 and 2013 in Romania show a trend of decline in the age at menarche estimated at 0.25 years in girls in urban areas and 1.08 years in those in rural areas (Pop et al, 2021). A review study gathered data on age at menarche in the Indonesian population found a downward trend from 14.43 to 13.23 years between 1961 and 2010 (Wahab et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Data from a Danish cohort of girls born between 2000 and 2003 estimated a menarche age of 13.0 years, occurring 3.6 months before the mothers’ menarche age (Brix et al, 2019). The data from five studies carried out between 1971 and 2013 in Romania show a trend of decline in the age at menarche estimated at 0.25 years in girls in urban areas and 1.08 years in those in rural areas (Pop et al, 2021). A review study gathered data on age at menarche in the Indonesian population found a downward trend from 14.43 to 13.23 years between 1961 and 2010 (Wahab et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had reported that the height of children and adults differed according to region (demographics) and social class [ 1 , 5 , 6 ]. The secular trend was affected by quality of life, urbanization, modernization, water and electricity access, nutrition, and health care [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different contrast agents may provide various levels of opacification [ 28 ], and, using a protocol targeted on the estimated body mass index [ 29 ], in our study, the images were acquired using the same contrast agent and the same protocol; therefore, they should provide similar enhancement and no differences in terms of dissection flap identification.…”
Section: Discussionmentioning
confidence: 99%